Functional Finishing of Viscose Knitted Fabrics via Graphene Coating. Issue 3 (September 2017) - Wu, Wen; Zhang, Huanxia; Ma, Hui; Cao, Jianda; Jiang, Lianyi; Chen, Guanglin
Functional finishing of viscose knitted fabrics was realized through layer-by-layer assembly with graphene oxide and reduction treatment of hydrazine hydrate. Due to the introduction of graphene, viscose fabrics became conductive, and exhibited enhanced anti-ultraviolet properties and hydrophobicity. Scanning electron microscopy results demonstrated that graphene could form thin films on the surface of viscose fibers, and with an increase in dipping-drying cycles, partial peeling of the thin films was observed. Electrical resistivity tests indicated that the volume resistance could reach to 128 Ω·cm and 96 Ω·cm when the courses and wales of the viscose fabrics treated for thirty dipping-drying cycles. In addition, ultraviolet protection factor of the viscose fabrics was 100+ and the water contact angle of the viscose fabrics treated for twelve cycles was 125 o compared with 18 o for the original fabrics. These multifunctional fabrics have potential applications in conductive devices, water treatment systems and smart textiles.